Joint and individual associations between multiple vitamins and sperm quality in adult men - Yao, Wen; Zhang, Juan; Yan, Weihong; Xie, Di; Tuo, Ping; Liu, Jie; Zhao, Xiaoling; Xiong, Yiwen; Li, Yang; Pan, Tiejun (Frontiers in Nutrition, 2025)
BackgroundSeveral studies have suggested that a healthy diet is associated with improved male fertility outcomes. However, the joint and individual associations between the status of multiple vitamins and sperm quality remain unclear.ObjectivesThis study aimed to investigate the associations between serum vitamin levels and sperm quality parameters in adult men.MethodsA cross-sectional study was conducted among 156 adult men seeking fertility care at a reproductive center from December 2023 to June 2024. Blood and semen were collected on the same day to determine the concentrations of nine kinds of vitamins (B1, B2, B6, B9, B12, C, A, D, E) and five parameters of sperm quality [total sperm number, sperm concentration, progressive motile sperm, morphologically normal rate, and DNA fragment index (DFI)]. The joint and individual associations between vitamin levels and sperm quality were analyzed using multiple linear regression and Bayesian kernel machine regression (BKMR) models.ResultsIncreased tertiles of vitamin B1 and 1,25-dihydroxyvitamin D3 [1,25–(OH)2-D3] in serum were associated with higher sperm quality (all P for trends < 0.10). Compared with the lowest tertiles, the highest tertiles of vitamin B12 had β: 3.0 (95% CI: 0.8, 5.2) increasing in DFI, and vitamin A was negatively associated with progressive sperm motility (P for trends = 0.05). We generally found null results between multiple vitamin levels and the parameters of sperm quality in the BKMR models.DiscussionThese research findings imply that vitamins could have a dose-dependent dual effect on sperm quality. More specifically, the impact of vitamins varies according to their dosage levels and types. Personalized vitamin supplementation may be more effective than taking multivitamins in improving sperm quality.